2014
DOI: 10.1016/j.bbr.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the nicotinic acetylcholine receptor agonists ABT-089 and ABT-107 attenuates the reinstatement of nicotine-seeking behavior in rats

Abstract: Current smoking cessation pharmacotherapies have modest efficacy, and most smokers relapse within the first few days after a quit attempt. Nicotine withdrawal-induced craving and cognitive impairments predict smoking relapse during abstinence and suggest that cognitive-enhancing drugs may prevent relapse. ABT-089 and ABT-107 are subtype-selective nAChR agonists that improve cognitive performance in laboratory animals. However, there are no studies examining the effects of ABT-089 and ABT-107 on nicotine self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Indeed, ABT-089 has cognition-enhancing properties (Decker et al, 1997, Lin et al, 1997), improves attention (Prendergast et al, 1998), reduces nicotine intake (Lee et al, 2014), reduces L-Dopa-induced dyskinesias in Parkinson’s disease models (Zhang et al, 2014), and has shown efficacy in human clinical trials for attention deficit hyperactivity disorder (Wilens et al, 2006). Although originally characterized as an α4β2-specific ligand, later pharmacology studies demonstrated significant activity at α6* nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ABT-089 has cognition-enhancing properties (Decker et al, 1997, Lin et al, 1997), improves attention (Prendergast et al, 1998), reduces nicotine intake (Lee et al, 2014), reduces L-Dopa-induced dyskinesias in Parkinson’s disease models (Zhang et al, 2014), and has shown efficacy in human clinical trials for attention deficit hyperactivity disorder (Wilens et al, 2006). Although originally characterized as an α4β2-specific ligand, later pharmacology studies demonstrated significant activity at α6* nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding animals, housing, surgery and acquisition of nicotine and sucrose self-administration can be found in Supplementary Materials and Methods and are identical to those described in our previously published studies. 10 , 11 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…However, his contributions extended to other neural targets including α -type peroxisome proliferator-activated receptors (PPAR α ) (Justinova et al 2015; Panlilio et al 2012), group II metabotropic glutamate receptors (mGluR2 and mGluR3) (Justinova et al 2015, 2016), dopamine receptors (Yan et al 2012), and α1-adrenoreceptors (Forget et al 2010). Clearly, the SA model has emerged as the gold standard for medication development (Chang et al 2015; Cippitelli et al 2015; George et al 2011; Lee et al 2014; Le Foll et al 2012; Levin et al 2008, 2010, 2011 O’Connor et al 2010; Rollema et al 2007a, 2007b; Shoaib and Buhidma 2016). …”
Section: Review Of Other Intravenous Nicotine Self-administration Resmentioning
confidence: 99%